Variation in prevalence of participation limitation, injury location, and training habits between young and master runners: A cross-sectional study - Rachel Berns; Jo Armour Smith; Natalia Sánchez; Samantha Jeffcoat; Susan Sigward; Andrew Hooyman; Shawn Farrokhi (PLoS ONE, 2026)
Background/Objectives Running is a popular form of physical activity, but its growing participation has been accompanied by high rates of injury that may limit ongoing engagement, particularly in older runners. This study explored differences in running participation limitation, injury location, and training characteristics between young (18–34 years) and master (>35 years) runners. Methods A total of 207 runners (105 young, 102 master) completed an online survey assessing demographics, training habits, and injury-related participation limitations using the updated Oslo Sports Trauma Research Center Overuse Injury Questionnaire. Results Master runners reported higher rates of injury-related participation limitation than young runners (51% vs. 34%, p = 0.04) and more upper extremity injuries (p < 0.01). They also had longer running histories, higher weekly mileage, and longer training durations (p < 0.05). Among master runners, increased odds of running participation limitation were associated with smoking [Odds Ratio (OR)=1.89], running on gravel/pebbled surfaces (OR=1.10), and owning more pairs of running shoes (OR=1.02), with no protective factors identified. Among young runners, reduced odds of running participation limitation were associated with running on off-road tracks (OR=0.68), having a running coach (OR=0.70), wearing shoes with special features (OR=0.75), and training on multiple surfaces (OR=0.79), while slightly increased odds were associated with longer average training sessions (OR=1.04) and running on grass (OR=1.08). Conclusion These findings highlight the high prevalence of running participation limitations, particularly in master runners, and support the need for age-specific training and injury prevention strategies. Implications Different age groups of runners may benefit from tailored risk mitigation strategies: young runners may benefit from coach-guided training, appropriate footwear selection, and varied training surfaces, while avoiding unnecessarily long sessions. For master runners, emphasis may be placed on screening for modifiable health risks (e.g., smoking), careful management of training load and surface exposure, and addressing upper-extremity complaints, given their higher prevalence of participation limitation.